Factors Related to College Major Selection in Communication Sciences and Disorders: Application of the Theory of Planned Behavior. - Ai Leen Choo; Gurevich, Naomi; Dadzie, Nana; Reidenbach, Kayla; Laxman, Malini; Ngo, Kelley (Perspectives of the ASHA Special Interest Groups, 2023)
Purpose: The growing number of racial and ethnic minorities in the United States is not reflected in the speech-language pathology profession, with ramifications for the diverse communities it serves. Despite decades of initiatives, the numbers of racial and ethnic minorities entering the profession have been modest. The aim of this pilot study is to explore potential factors that influence decision making for a college major that could inform strategies for underrepresented racial and ethnic minority (URM) recruitment into communication sciences and disorders (CSD) programs. Method: The theory of planned behavior was used as a framework to explore the influences on students' selection of college majors with a particular focus on speech-language pathology. Students enrolled and not enrolled in CSD programs were surveyed about their attitudes, perceived behavioral control, and subjective normative pressure (e.g., perceptions of race and ethnic representation, familiarity with speech-language pathology, and family education). Results: There were significant differences between CSD and non-CSD respondents, and between URM and White respondents in their perception of representation and exposure to the profession. The majority of URM students reported that race and ethnic representation is important in their chosen job. URM students were less likely than White students to know anyone who has received speech-language therapy or who is a speech-language pathologist. Conclusion: Findings suggest that initiatives to increase representation and diverse role models, and early exposure to the profession for URM students should be areas of focus in the efforts to diversify the profession.